Economic for humans - "Nelson, Julie A" (Chicago, 2006)
In this volume views important social and political issues through the eyes of economists. This approach asserts that all actions, whether working, playing, dating, or mating, have economic motivations and consequences, and can be analysed using economic reasoning. Intended as an introduction to the current state of the field, the essays are informal and non-technical, while still using up-to-date economic reasoning to illuminate such topics as crime, marriage, discrimination, immigration, fads and fashions. The expanding domain of economics is illustrated, as problems from sociology, political science, anthropology, and public policy are all included
Keywords: Economics-Moral & ethical aspects